2000
DOI: 10.1080/11250000009356296
|View full text |Cite
|
Sign up to set email alerts
|

Winter roost occupancy and behaviour at evening departure of urban long‐eared owls

Abstract: Roost occupancy and behaviour at evening departure were studied in long-eared owls (Asio otus) at a large winter roost in the southern suburbs of the city of Milan, northern Italy. The number of roosting owls was strongly correlated with decreasing daylength, while it was weakly negatively correlated with temperature. Hence changes in photoperiod can be considered among the proximate factors promoting the winter aggregation of longeared owls. Behaviour at departure was influenced by cloud cover: birds departed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…During the study period, the number of long-eared owls changed on a convex curve, with the maximum occurring from the end of November to the middle of December ( Figure 2). According to the literature, the maximum number of long-eared owls was in December in Milan, in Southern Europe [9], or with the peak in December or January in Moscow, in the north of the winter range [10]. In Romania, the number of owls was the highest in February and in November [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, the number of long-eared owls changed on a convex curve, with the maximum occurring from the end of November to the middle of December ( Figure 2). According to the literature, the maximum number of long-eared owls was in December in Milan, in Southern Europe [9], or with the peak in December or January in Moscow, in the north of the winter range [10]. In Romania, the number of owls was the highest in February and in November [11].…”
Section: Resultsmentioning
confidence: 99%
“…The literature on roosting sites and attendant behaviour is limited, and few of the existing observations have been systematic [5,8]. Furthermore, relatively little work has been carried out on other aspects of the biology of this species, such as the phenology of winter roost occupancy and behaviour at the roost [9]. This ecology aspect has not been studied in Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…rats) or gregarious prey species (e.g. birds: Mori and Bertolino, 2015), which provide it with highly profitable, easily captured prey items (Wijnandts, 1984;Pirovano et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…It subsequently showed up in the winter roost A where it stayed for the rest of the wintering. The reason for these relocations during the winter may be a sudden change of the meteorological factors highly impacting on the diet of long-eared owls , just as on the number of wintering long-eared owls itself (Pirovano et al, 2000). The other reason for the relocation to another winter roost may be a human disturbance (Noga, 2007) or other impacts and their combination.…”
Section: Discussionmentioning
confidence: 99%
“…Galleotti et al (1997), Martínez, Zubergoitia (2004), Lövy, Riegert (2013) have observed the preference of this part of the land. The number of wintering individuals changing during the winter (Noga, 2007;Pirovano et al, 2000) and their abundance culminating in December (Wijnandts, 1984) point out the fact that long-eared owls may change the particular winter roosts. It is only Wijnandts (1984) who describes the abandonment of winter roosts and the movement of the individuals between the winter roosts during the winter, however, without any specific facts.…”
Section: Discussionmentioning
confidence: 99%